Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Konsumen: ( Studi Pada Mahasiswa Pengguna Ojek Konvensional) - Dimas Realino; Valeria Eldyn Gula; Sofiana Jelita (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
Conventional Ojek is one form of alternative transportation in Indonesia. Sikka Regency has rapid development in all sectors and has several airports and ports to support the movement of people and goods. Conventional ojek meets the biggest competitor, namely the emergence of online ojek. Although various competitors appear conventional ojek in Sikka Regency is still the main choice of public transportation mode. This study analyzes the effect of service quality and price on consumer satisfaction of students who use conventional ojek services at Nusa Nipa University. The population in this study were all students who use conventional ojek at Nusa Nipa University. This study uses purposive sampling method, namely the technique of determining the sample using certain considerations with the number of respondents 100 people. The research instrument used a questionnaire with the data collection technique used was to use a Likert scale and analyzed using SPSS 25 software. The results show that partially service quality has a significant effect on customer satisfaction. Price has a significant effect on customer satisfaction. Simultaneously service quality and price have a significant effect on customer satisfaction. Conventional ojek has become a means of transportation that is needed by people in Maumere city. Government advice needs to take care of legalization, conventional ojek data collection, infrastructure management and price regulations and to ojek drivers pay attention to safety, comfort and completeness of vehicles.